The Influence of Client-Centered Counseling with Self-Reflection on Overthinking Behavior of a Bilingual Islamic Boarding School Student - Sholihah, Maidatus; Ningsih, Yusria (Tafkir: Interdisciplinary Journal of Islamic Education, 2024)
This research explores an innovative approach to dealing with overthinking behavior in Santri at the Bilingual Islamic Boarding School in Krian, Sidoarjo, through Client-Centered Counseling with Self-Reflection (Muhasabah Diri). This topic involves counseling and psychology, focusing on changing the client's behavior and outlook. This study aims to test the hypothesis that the integration of Client-Centered Counseling with Self-Muhasabah will effectively reduce the level of overthinking among Santri. Using a quantitative method with a single-subject design of A1-B-A2, this study observed behavior before and after the counseling session. Data were collected through observation, interviews, and questionnaires to measure the level of psychological distress. The results showed significant behavioral changes after the counseling sessions. Before counseling, the client showed overthinking behavior that led to self-doubt, excessive worry, anxiety, and difficulty adapting. After counseling, clients showed increased confidence in social situations, were calmer in facing challenges, and were more courageous in interacting with others, especially new people. This research highlights that Client-Centered Counseling with Self-Reflection is effective in overcoming overthinking behavior in students. The integration of Client-Centered Counseling which emphasizes active client involvement and Self-Reflection which focuses on introspection provides a comprehensive and relevant solution. This research contributes by examining the impact of this approach on the emotional, intellectual, physiological, and interpersonal aspects of student, supporting their personal, social, and spiritual development. By enhancing mental and spiritual well-being, this research offers new insights into educational strategies that address the well-being of students.